Effects of Dexamethasone and Pentoxifylline on Mania-like and Depression-like Behaviors in Rats - Ahmad Nassar; Abed N. Azab (MDPI AG, 2022)
Several studies support the notion that inflammation plays a role in the pathophysiology and treatment approaches of psychiatric illnesses, particularly mood disorders. Congruently, classic anti-inflammatory drugs were found efficacious in randomized clinical trials of patients with mood disorders. Moreover, accumulating data indicate that psychotropic drugs exhibit some anti-inflammatory effects. This study was undertaken to examine the efficacy of dexamethasone (a potent corticosteroid) and pentoxifylline (a methylxanthine drug with proven anti-tumor necrosis factor-α inhibitory activity) in behavioral models in rats, which were treated intraperitoneally with either dexamethasone or pentoxifylline for two weeks and then subjected to a battery of behavioral tests. Treatment with pentoxifylline, but not dexamethasone, was associated with antidepressant-like and anti-manic-like effects. The beneficial behavioral effects of pentoxifylline were accompanied by a prominent reduction in pro-inflammatory mediator levels in the brain. For the first time, the current work proves the efficacy of pentoxifylline against both mania-like and depressive-like behaviors. These results suggest that pentoxifylline may be a promising therapeutic intervention for patients with mood disorders. Taking into account the excellent tolerability profile of pentoxifylline in humans, it is warranted to conduct randomized clinical trials to investigate its therapeutic efficacy in patients with psychiatric disorders.